ANALISIS PERBEDAAN KUANTITAS PRODUCT SALES ANTAR DEPARTMENT PERIODE BULAN JUNI 2023 PADA SALAH SATU CUSTOMER DI PT X - Jesica Hutagalung; Sabarinsyah (LPPM-ITEBA, 2023)
This study aims to see whether there are differences in the number of sales between departments to a customer at PT. XManufacturing Indonesia for one month. The data used is sales data to one of the customers in June 2023. The analysis used to test the data is the Analysis of Variance. The test results show a significance value of 0.039, so that the sig or P value <0.05. So it can be concluded that there is a significant difference between the quantity of sales between departments. This is directly proportional to the ANOVA test conducted to determine the difference in average sales between departments.